Dalil Hukum Perjanjian Perkawinan - Saphira Husna Nasution; Mhd. Amar Adly; Heri Firmansyah (Jurnal Kajian dan Penelitian Umum, 2025)
This article elaborates on the definition of marriage agreements, the procedures for establishing such agreements, their benefits, and the religious evidence addressing the topic. The study employs a qualitative descriptive methodology and a library research technique. The arguments presented in this essay are based on various sources, including hadiths, tafsir, fiqh literature, and classical Islamic texts. It also incorporates the arguments and opinions of Islamic scholars. Contributions from modern fiqh experts are also included, resulting in a cohesive conclusion. The findings of this study indicate that, based on evidence from the Quran, Hadith, and the majority of scholars (jumhur ulama), the legal ruling on marriage agreements is permissible (mubah).